Perkembangan Resistensi Wereng Batang Padi Cokelat (Nilaparvata lugens Stal) di Sentra Produksi Padi Kabupaten Tanjung Jabung Barat dan Tanjung Jabung Timur - Yuni Ratna; Wilma Yunita; Elly Indra Swari; Dea Diyan Putri; Rahayu Hermita Sinaga (Universitas Batanghari, 2022)
The research took place from June-October 2020 at the rice production centersin Tanjung Jabung Barat and Tanjung Jabung Timur regency Jambi province. The resistance test of Nilaparvata lugens to the active ingredients of insecticide was carried out at the Pesticide and Weed Laboratory, Faculty of Agriculture, Jambi University. This study aimed to determine the resistance level of N. lugens of Rawa Medang and Sri Agung population (Batang Asam district, Tanjung Jabung Barat regency), and Parit Culum II and Teluk Dawan population (Muara Sabak district, Tanjung Jabung Timur regency) to the insecticides used. The active ingredients of insecticide tested were abamektin and dimehipo (N. lugens of Rawa Medang and Sri Agung population), and BPMC and fipronil (N. lugens of Parit Culum II and Teluk Dawan population). Mass rearing of N. lugens was carried out at the Pesticide and Weeds Laboratory using Ciherang variety as feed. Insecticide toxicity test on macroptera female adults of N. lugens was carried out by the feed dipping method with two stages, namely preliminary and main tests. Preliminary test was carried out on N. lugens field population 2nd generation (F2), while main test was carried out on field population (F2) and standard population (F41). The observed variables were N. lugens mortality and resistance ratio (NR). Mortality data of N. lugens at 72 hours after insecticide application was analyzed probit using the PoloPlus program. The results showed that N. lugens of Rawa Medang population has been resistant (NR=6.2) to abamektin and indicated to be resistant to dimehipo (NR=1.5), while Sri Agung population was indicated to be resistant to abamektin (NR=2.9) and dimehipo (NR=1.5). N. lugens of Parit Culum II population has been resistant to BPMC (NR=4.94) and fipronil (NR=44.62), while Teluk Dawan population was indicated to be resistant to BPMC (NR=2.76)